Is biceps femoris aponeurosis size an independent risk factor for strain injury? - Freitas, S. R.; Abrantes, F.; Santos, F.; Mascarenhas, V.; Oliveira, R.; Firmino, T.; Mendes, B.; Cerda, M.; Vaz, J. R. (International Journal of Sports Medicine, 2020)
This study examined whether professional footballers with previous biceps femoris long head (BFLH) injury in the last 3-years present a smaller proximal aponeurosis (Apo-BFLH) size compared to footballers with no previous injury. We examined the Apo-BFLH and BFLH size using magnetic resonance imaging and tested the knee flexor maximal isometric strength in 80 thighs of 40 footballers. Apo-BFLH size parameters were processed using a semi-automated procedure. Outcomes were compared between thighs with (n=9) vs. without (n=71) previous BFLH injury. No differences were observed between injured and non-injured thighs for the Apo-BFLH and BFLH size parameters (p>0.05) except for Apo-BFLH volume, which was higher in the non-injured thighs of athletes with previous injury (3692.1±2638.4 mm3, p<0.006) compared to the left (2274.1±798.7 mm3) thighs of athletes without previous injury. A higher knee flexor isometric strength was observed in the injured limb of athletes with previous BFLH injury (196.5±31.9 Nm, p<0.003) compared to the left (156.2±31.4 Nm) and right (160.0±31.4 Nm) thighs of non-injured athletes. The present results suggest that BFLH proximal aponeurosis size should not be considered as an independent risk factor for strain injury.